Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Individual and multi-environment combined analyses identify QTLs for morphogenetic and reproductive development traits in white clover (Trifolium repens L.) - N. O. I. Cogan; M. T. Abberton; K. F. Smith; G. Kearney; A. H. Marshall; A. Williams; T. P. T. Michaelson-Yeates; C. Bowen; E. S. Jones; A. C. Vecchies; J. W. Forster (Theoretical and Applied Genetics, 2006)

The nature of spatial transitions in the Arctic - H. E. Epstein; J. Beringer; W. A. Gould; A. H. Lloyd; C. D. Thompson; F. S. Chapin; G. J. Michaelson; C. L. Ping; T. S. Rupp; D. A. Walker (Journal of Biogeography, 2004)
Aim Describe the spatial and temporal properties of transitions in the Arctic and develop a conceptual understanding of the nature of these spatial transitions in the face of directional environmental change. Location Arctic tundra ecosystems of the North Slope of Alaska and the tundra‐forest region of the Seward Peninsula, Alaska Methods We synthesize information from numerous studies on tundra and treeline ecosystems in an effort to document the spatial changes that occur across four arctic transitions. These transitions are: (i) the transition between High‐Arctic and Low‐Arctic systems, (ii) the transition between moist non‐acidic tundra (MNT) and moist acidic tundra (MAT, also referred to as tussock tundra), (iii) the transition between tussock tundra and shrub tundra, (iv) the transition between tundra and forested systems. By documenting the nature of these spatial transitions, in terms of their environmental controls and vegetation patterns, we develop a conceptual model of temporal dynamics of arctic ecotones in response to environmental change. Results Our observations suggest that each transition is sensitive to a unique combination of controlling factors. The transition between High and Low Arctic is sensitive primarily to climate, whereas the MNT/MAT transition is also controlled by soil parent material, permafrost and hydrology. The tussock/shrub tundra transition appears to be responsive to several factors, including climate, topography and hydrology. Finally, the tundra/forest boundary responds primarily to climate and to climatically associated changes in permafrost. There were also important differences in the demography and distribution of the dominant plant species across the four vegetation transitions. The shrubs that characterize the tussock/shrub transition can achieve dominance potentially within a decade, whereas spruce trees often require several decades to centuries to achieve dominance within tundra, and Sphagnum moss colonization of non‐acidic sites at the MNT/MAT boundary may require centuries to millennia of soil development. Main conclusions We suggest that vegetation will respond most rapidly to climatic change when (i) the vegetation transition correlates more strongly with climate than with other environmental variables, (ii) dominant species exhibit gradual changes in abundance across spatial transitions, and/or (iii) the dominant species have demographic properties that allow rapid increases in abundance following climatic shifts. All three of these properties characterize the transition between tussock tundra and low shrub tundra. It is therefore not surprising that of the four transitions studied this is the one that appears to be responding most rapidly to climatic warming.

Relationships between genetic distance measured by RAPD-PCR and heterosis in inbred lines of white clover (Trifolium repens L.) - Toby A. Joyce; Michael T. Abberton; T.P.T. Michaelson-Yeates; John W. Forster (Euphytica, 1999)